Theory of an improved vertical power MOSFET using high-k insulator. (December 2015) - Huang, Mingmin; Chen, Xingbi
Abstract: An improved structure of the vertical power MOSFET using high- k insulator (H k -MOSFET), which has a better relationship between specific on-resistance ( R on ) and breakdown voltage ( V B ) than the conventional H k -MOSFET and the superjunction MOSFET, is studied. An analytic model of this improved H k -MOSFET is proposed, which can be used to well explain the physical reason of the improvement as well as to obtain an optimal design. It is found that the theoretical results match well with the numerical simulation results, where the errors of V B and R on are both less than 7%. Moreover, the numerical simulation results show that, with the guidance of the proposed analytic model, R on of the improved H k -MOSFET can be optimized to be about 30%–50% lower than that of the conventional H k -MOSFET with V B = 300–1000 V. Highlights: An improved structure of the H k -MOSFET is studied. An analytical model is proposed for design and optimization of it. The model helps to understand the physical reason of the improvement. The improved H k -MOSFET has a lower R on than the SJ-MOSFET. The H k -MOSFET has a more robust V B against deviations of doping dose than SJ-MOSFET.